A case report of multisite arterial thrombosis in a patient with coronavirus disease 2019 (COVID-19). Issue 1 (21st December 2020) - Angelillis, Marco; De Carlo, Marco; Christou, Andrea; Marconi, Michele; Mocellin, Davide M; Caravelli, Paolo; De Caterina, Raffaele; Petronio, Anna S
Abstract: Background: A systemic coagulation dysfunction has been associated with COVID-19. In this case report, we describe a COVID-19-positive patient with multisite arterial thrombosis, presenting with acute limb ischaemia and concomitant ST-elevation myocardial infarction and oligo-symptomatic lung disease. Case summary: An 83-year-old lady with history of hypertension and chronic kidney disease presented to the Emergency Department with acute-onset left leg pain, pulselessness, and partial loss of motor function. Acute limb ischaemia was diagnosed. At the same time, a routine ECG showed ST-segment elevation, diagnostic for inferior myocardial infarction. On admission, a nasopharyngeal swab was performed to assess the presence of SARS-CoV-2, as per hospital protocol during the current COVID-19 pandemic. A total-body CT angiography was performed to investigate the cause of acute limb ischaemia and to rule out aortic dissection; the examination showed a total occlusion of the left common iliac artery and a non-obstructive thrombosis of a subsegmental pulmonary artery branch in the right basal lobe. Lung CT scan confirmed a typical pattern of interstitial COVID-19 pneumonia. Coronary angiography showed a thrombotic occlusion of the proximal segment of the right coronary artery. Percutaneous coronary intervention was performed, with manual thrombectomy, followed by deployment of two stents. The patient was subsequently transferred to the operating room, where a Fogarty thrombectomy was performed. The patient was then admitted to the COVID area of our hospital. Seven hours later, the swab returned positive for COVID-19. Discussion: COVID-19 can have an atypical presentation with thrombosis at multiple sites.